Control of dominant conduction orbitals by peripheral substituents in paddle-wheel diruthenium alkynyl molecular junctions. Issue 32 (20th July 2021) - Ogawa, Shiori; Chattopadhyay, Swarup; Tanaka, Yuya; Ohto, Tatsuhiko; Tada, Tomofumi; Tada, Hirokazu; Fujii, Shintaro; Nishino, Tomoaki; Akita, Munetaka
Abstract : Dominant conduction orbitals of paddle-wheel organodiruthenium complexes can be facilely controlled by the substituents embedded in the amidinato ligands. Abstract : Control of charge carriers that transport through the molecular junctions is essential for thermoelectric materials. In general, the charge carrier depends on the dominant conduction orbitals and is dominantly determined by the terminal anchor groups. The present study discloses the synthesis, physical properties in solution, and single-molecule conductance of paddle-wheel diruthenium complexes 1 R having diarylformamidinato supporting ligands (DArF: p -R-C6 H4 -NCHN-C6 H4 -R- p ) and two axial thioanisylethynyl conducting anchor groups, revealing unique substituent effects with respect to the conduction orbitals. The complexes 1 R with a few different aryl substituents (R = OMe, H, Cl, and CF3 ) were fully characterized by spectroscopic and crystallographic analyses. The single-molecule conductance determined by the scanning tunneling microscope break junction (STM-BJ) technique was in the 10 −5 to 10 −4 G 0 region, and the order of conductance was 1 OMe > 1 CF3 ≫ 1 H ∼ 1 Cl, which was not consistent with the Hammett substituent constants σ of R. Cyclic voltammetry revealed the narrow HOMO–LUMO gaps of 1 R originating from the diruthenium motif, as further supported by the DFT study. The DFT-NEGF analysis of this unique result revealed that the dominant conductance routes changed from HOMO conductance (for 1 OMe ) to LUMO conductance (for 1 CF3 ). The drastic change in the conductance properties originates from the intrinsic narrow HOMO–LUMO gaps.